Intersecting stigma and HIV testing practices among urban refugee adolescents and youth in Kampala, Uganda: qualitative findings. Issue 3 (13th March 2021) - Logie, Carmen H; Okumu, Moses; Kibuuka Musoke, Daniel; Hakiza, Robert; Mwima, Simon; Kyambadde, Peter; Abela, Heather; Gittings, Lesley; Musinguzi, Joshua; Mbuagbaw, Lawrence; Baral, Stefan
Abstract: Introduction: HIV‐related risks may be exacerbated in humanitarian contexts. Uganda hosts 1.3 million refugees, of which 60% are aged under 18. There are knowledge gaps regarding HIV testing facilitators and barriers, including HIV and intersecting stigmas, among urban refugee youth. In response, we explored experiences and perspectives towards HIV testing strategies, including HIV self‐testing, with urban refugee youth in Kampala, Uganda. Methods: We implemented a qualitative study with refugee cisgender youth aged 16 to 24 living in Kampala's informal settlements from February‐April 2019. We conducted five focus groups with refugee youth, including two with adolescent boys and young men, two with adolescent girls and young women and one with female sex workers. We also conducted five key informant (KI) interviews with government, non‐government and community refugee agencies and HIV service providers. We conducted thematic analyses to understand HIV testing experiences, perspectives and recommendations. Results: Participants (n = 49) included young men (n = 17) and young women (n = 27) originally from the Democratic Republic of Congo [DRC] (n = 29), Rwanda (n = 11), Burundi (n = 3) and Sudan (n = 1), in addition to five KI (gender: n = 3 women, n = 2 men; country of origin: n = 2 Rwanda, n = 2 Uganda, n = 1 DRC). Participant narratives revealed stigma drivers included fear of HIV infection; misinformation that HIV is a "Ugandan disease"; and blame and shame for sexual activity. Stigma facilitators included legal precarity regarding sex work, same‐sex practices and immigration status, alongside healthcare mistreatment and confidentiality concerns. Stigma experiences were attributed to the social devaluation of intersecting identities (sex work, youth, refugees, sexual minorities, people living with HIV, women). Participants expressed high interest in HIV self‐testing. They recommended HIV self‐testing implementation strategies to be peer supported and expressed concerns regarding sexual‐ and gender‐based violence with partner testing. Conclusions: Intersecting stigma rooted in fear, misinformation, blame and shame, legal precarity and healthcare mistreatment constrain current HIV testing strategies with urban refugee youth. Findings align with the Health Stigma and Discrimination Framework that conceptualizes stigma drivers and facilitators that devalue intersecting health conditions and social identities. Findings can inform multi‐level strategies to foster enabling HIV testing environments with urban refugee youth, including tackling intersecting stigma and leveraging refugee youth peer support.